An investigation into the potential immunogenicity of various extracts of the South African bont tick Amblyomma hebraeum - Adamson, Deborah Jane (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1993)
Rabbits and goats were inoculated with crude, membrane-associated and soluble components extracted from unengorged adult females and nymphs of the bont tick Amblyomma hebraeum. Inoculation provided some protection against nymphal infestation, however it had little effect on adult feeding. Histological examination of adults fed on inoculated hosts showed evidence of gut damage. Skin provocation testing with tick extracts elicited a Type I immediate hypersensitivity which was influenced by antihistamine. A delayed skin reaction was also evident. Whether this was attributable to Type III Arthus reaction or Type IV cell-mediated hypersensitivity was not determined. A comparative histological study of sites of tick extract injection, on inoculated and naive hosts, demonstrated the role of eosinophils in the hosts response to tick feeding. Serological examination revealed elevated anti-A hebraeum lgG titres following inoculation. These titres were found to decrease in the ten weeks after inoculation, despite the hosts being repeatedly infested with A hebraeum. Although the IgG titres of naive control hosts increased after each tick infestation, they failed to reach the titres achieved through inoculation. Western blot analysis of serum from inoculated hosts recognized most of the A. hebraeum proteins against which it was screened.
Keywords: Amblyomma -- South Africa; Ticks -- South Africa; Ticks -- Control -- South Africa